2021
DOI: 10.21100/compass.v14i3.1219
|View full text |Cite
|
Sign up to set email alerts
|

Staff and student perspectives of online teaching and learning; implications for belonging and engagement at university – a qualitative exploration

Abstract: A sense of belonging within higher education (HE) enhances educational engagement and attainment. The rapid shift to online provision has implications for reducing students’ sense of belonging at university. We have previously shown that students consider belonging in HE to be important and that their personal sense of belonging was high. We also found that sense of belonging had elements of people and place: relationships with peers and staff were influential and the physical campus facilitated social relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It calls for necessary continuous professional development that should include the development of both digital and psycho-pedagogical competence, with a focus on effective course design, instruction, implementation and evaluation (Nawar Al-Saadi, 2017). Pedagogically, there is also a need to adapt and adjust the teaching methods to the specificity of the online process (Kim & Bonk, 2006), which is why studies providing echoes of the experiences of trained teachers/experts on the topic are useful (Thomas & Dello Stritto, 2021);  Students' perspective on the process Duţă, 2023;Nikolenko et al, 2023;Islam & Mondal, 2022;Laili & Nashir, 2022;Lamanauskas et al, 2022;Radmehr & Goodchild, 2022;Soliman et al, 2022;Abu et al, 2021;Alexa, 2021;Almahasees et al, 2021;Aziz Ansari et al, 2021;Fyllos et al, 2021;Hofer et al, 2021;Saurabh et al, 2021;Seifert, 2021;Ayu, 2020;Coman et al, 2020;Mishra et al, 2020;Sadiku et al, 2018;Brittany, 2015). The data highlighted by such studies underline the need for a joint teacherstudent effort and a stronger commitment from both partners to create an online learning community that ensures a higher level of interaction and collaboration (Thomas & Dello Stritto, 2021;Kim & Bonk, 2006) between them as well as between students (Nawar Al-Saadi, 2017);  Views on the benefits and challenges of online teaching and online learning in the academic environment Nikolenko et al, 2023;Blonder et al, 2022;Radmehr & Goodchild, 2022;Soliman et al, 2022;Alexa, 2021;Aziz Ansari et al, 2021;Bekker & Nazir, 2021;…”
Section: Studies Focused On Exploring the Online Teaching-learning Pr...mentioning
confidence: 99%
“…It calls for necessary continuous professional development that should include the development of both digital and psycho-pedagogical competence, with a focus on effective course design, instruction, implementation and evaluation (Nawar Al-Saadi, 2017). Pedagogically, there is also a need to adapt and adjust the teaching methods to the specificity of the online process (Kim & Bonk, 2006), which is why studies providing echoes of the experiences of trained teachers/experts on the topic are useful (Thomas & Dello Stritto, 2021);  Students' perspective on the process Duţă, 2023;Nikolenko et al, 2023;Islam & Mondal, 2022;Laili & Nashir, 2022;Lamanauskas et al, 2022;Radmehr & Goodchild, 2022;Soliman et al, 2022;Abu et al, 2021;Alexa, 2021;Almahasees et al, 2021;Aziz Ansari et al, 2021;Fyllos et al, 2021;Hofer et al, 2021;Saurabh et al, 2021;Seifert, 2021;Ayu, 2020;Coman et al, 2020;Mishra et al, 2020;Sadiku et al, 2018;Brittany, 2015). The data highlighted by such studies underline the need for a joint teacherstudent effort and a stronger commitment from both partners to create an online learning community that ensures a higher level of interaction and collaboration (Thomas & Dello Stritto, 2021;Kim & Bonk, 2006) between them as well as between students (Nawar Al-Saadi, 2017);  Views on the benefits and challenges of online teaching and online learning in the academic environment Nikolenko et al, 2023;Blonder et al, 2022;Radmehr & Goodchild, 2022;Soliman et al, 2022;Alexa, 2021;Aziz Ansari et al, 2021;Bekker & Nazir, 2021;…”
Section: Studies Focused On Exploring the Online Teaching-learning Pr...mentioning
confidence: 99%
“…One of the reasons for this was campuses facilitation of social relationships, potentially though ease of meeting spaces (Mulrooney and Kelly, 2020a). Whilst social facilitation may play a role, Abu et al (2021) found that some students missed campus during online learning because of the perceived connections between sense of belonging and campus spaces, independent of social ties.…”
Section: The University Campus As a Hub For Belongingmentioning
confidence: 99%
“…What has become clear is that failure to give due attention to the affective (social) dimensions of the student's higher education experience is likely to be costly (Abu et al 2021). Brodie and Osowska (2021) note that there is still a dearth of understanding as to what a sense of belonging might entail in the online space and contend that intentional curriculum design and delivery that foregrounds this affective dimension is crucial.…”
Section: Lecturers' Pedagogical Competence Belonging Perceived Stress...mentioning
confidence: 99%